A Wireless Multi-Objective Power Sharing Method for Energy Storage System in DC Micro-Grid Considering Oscillatory-Type Power - YANG Jie; SUN Zhe; SU Xinyi; LU Gang; YUAN Bo (发电技术, 2024)
As the construction of new power systems, DC microgrids will become an important part of the distribution network. As AC load connecting to DC microgrids, the oscillating power will enter the DC system, which affects the power distribution of energy storage system. To solve this issue, the comprehensive principle of power distribution of distributed energy storage system was given, and a wireless power sharing method was proposed. This method takes the charge state as the “information carrier”, each energy storage unit can realize state of charge (SOC) balancing and oscillating power sharing at same time. In addition, from the perspective of equivalent output impedance, this paper gived a detailed analysis and discussion on the distribution effect of different control algorithms, which showed the proposed control algorithm could meet the requirements of the comprehensive principle. Finally, the effectiveness of the proposed distributed energy storage control strategy was validated by experiments.